2014
DOI: 10.1073/pnas.1410431111
|View full text |Cite
|
Sign up to set email alerts
|

Conformational cycle and ion-coupling mechanism of the Na + /hydantoin transporter Mhp1

Abstract: Ion-dependent transporters of the LeuT-fold couple the uptake of physiologically essential molecules to transmembrane ion gradients. Defined by a conserved 5-helix inverted repeat that encodes common principles of ion and substrate binding, the LeuTfold has been captured in outward-facing, occluded, and inwardfacing conformations. However, fundamental questions relating to the structural basis of alternating access and coupling to ion gradients remain unanswered. Here, we used distance measurements between pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(159 citation statements)
references
References 45 publications
9
148
2
Order By: Relevance
“…Structure and structure-function relationships of macromolecules are areas of intense EPR effort [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Coupled with site-directed spin-labeling (SDSL), EPR is oftentimes used to characterize protein and nucleic acid structures and dynamics, conformational changes, molecule folding, macromolecule complexes, and oligomeric structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure and structure-function relationships of macromolecules are areas of intense EPR effort [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Coupled with site-directed spin-labeling (SDSL), EPR is oftentimes used to characterize protein and nucleic acid structures and dynamics, conformational changes, molecule folding, macromolecule complexes, and oligomeric structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]17].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with site-directed spin-labeling (SDSL), EPR is oftentimes used to characterize protein and nucleic acid structures and dynamics, conformational changes, molecule folding, macromolecule complexes, and oligomeric structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]17]. The majority of biomolecules do not contain unpaired electrons from which one can obtain an EPR signal; therefore, spin-labeling approaches have been developed [15,[18][19][20][21][22][23][24][25] where site-specific persistent radicals or paramagnetic metal-probes are incorporated at specific locations within a biomolecule.…”
Section: Introductionmentioning
confidence: 99%
“…They have offered an essential molecular context for the investigation of the mechanism of uphill neurotransmitter reuptake transport enabled by the coupling with the transmembrane Na + gradient 1,10 . Our current understanding of functional mechanisms in NSS has been further shaped by the large body of structure-function studies of LeuT and other related bacterial transporters, carried out both experimentally [11][12][13][14][15][16][17] and computationally [11][12][13][14]16,[18][19][20][21][22][23] , and more recently by findings from molecular dynamics (MD) simulations of DAT [24][25][26][27][28][29] and SERT 30,31 constructs. Together, these studies have suggested for the transport cycle in NSS proteins an allosteric process that is consistent with the alternating access mechanism 32 in which concerted dynamic rearrangements on the extracellular (EC) and intracellular (IC) sides of the transporter result from ion-and ligand-specific conformational rearrangements.…”
mentioning
confidence: 99%
“…In addition, the lipid dependency of the conformational-energy landscape has been evaluated [139]. The SLC6A family, which is better known as LeuT family, has been exemplified based on the Na + -coupled amino acid symporter LeuT [140,141]), the Na + /hydantoin symporter Mhp1 [142] and the Na + /proline symporter PutP [143][144][145][146]. All studies are in agreement with the suggested combination of the rocker-switch and gating-type mechanisms in order to achieve alternating access.…”
Section: Secondary Active Proteinsmentioning
confidence: 99%